##### About Equation ASC.2.3.2.2
top up back next into bottom

Absolute reference: ASC:asympt:1:genfrec
###### LaTeX encoding
top up back next into bottom
2 u (n) \biggl(\frac{1}{2} + n\biggr) n + u (n - 1) \biggl(-\frac{1}{2} + n\biggr) \biggl(-\frac{1}{2} + 3 n\biggr) + u (n - 2) \biggl(-\frac{3}{2} + n\biggr) \biggl(-\frac{1}{2} + n\biggr) = \\ \quad{}\quad{}0
###### Maple encoding
2*u(n)*(1/2+n)*n+u(n-1)*(-1/2+n)*(-1/2+3*n)+u(n-2)*(-3/2+n)*(-1/2+n) = 0
###### MathML encoding
top up back next into bottom
<math xmlns='http://www.w3.org/1998/Math/MathML'><semantics><mrow xref='id38'><mrow xref='id36'><mrow xref='id9'><mrow><mrow><mn xref='id1'>2</mn><mo>&InvisibleTimes;</mo><mrow xref='id4'><mi xref='id2'>u</mi><mo>&ApplyFunction;</mo><mfenced><mi xref='id3'>n</mi></mfenced></mrow></mrow><mo>&InvisibleTimes;</mo><mfenced><mrow xref='id7'><mfrac xref='id5'><mn>1</mn><mn>2</mn></mfrac><mo>+</mo><mi xref='id6'>n</mi></mrow></mfenced></mrow><mo>&InvisibleTimes;</mo><mi xref='id8'>n</mi></mrow><mo>+</mo><mrow xref='id23'><mrow><mrow xref='id14'><mi xref='id10'>u</mi><mo>&ApplyFunction;</mo><mfenced><mrow xref='id13'><mi xref='id11'>n</mi><mo>-</mo><mn xref='id12'>1</mn></mrow></mfenced></mrow><mo>&InvisibleTimes;</mo><mfenced><mrow xref='id17'><mfrac xref='id15'><mn>-1</mn><mn>2</mn></mfrac><mo>+</mo><mi xref='id16'>n</mi></mrow></mfenced></mrow><mo>&InvisibleTimes;</mo><mfenced><mrow xref='id22'><mfrac xref='id18'><mn>-1</mn><mn>2</mn></mfrac><mo>+</mo><mrow xref='id21'><mn xref='id19'>3</mn><mo>&InvisibleTimes;</mo><mi xref='id20'>n</mi></mrow></mrow></mfenced></mrow><mo>+</mo><mrow xref='id35'><mrow><mrow xref='id28'><mi xref='id24'>u</mi><mo>&ApplyFunction;</mo><mfenced><mrow xref='id27'><mi xref='id25'>n</mi><mo>-</mo><mn xref='id26'>2</mn></mrow></mfenced></mrow><mo>&InvisibleTimes;</mo><mfenced><mrow xref='id31'><mfrac xref='id29'><mn>-3</mn><mn>2</mn></mfrac><mo>+</mo><mi xref='id30'>n</mi></mrow></mfenced></mrow><mo>&InvisibleTimes;</mo><mfenced><mrow xref='id34'><mfrac xref='id32'><mn>-1</mn><mn>2</mn></mfrac><mo>+</mo><mi xref='id33'>n</mi></mrow></mfenced></mrow></mrow><mo>=</mo><mn xref='id37'>0</mn></mrow><annotation-xml encoding='MathML-Content'><apply id='id38'><eq/><apply id='id36'><plus/><apply id='id9'><times/><cn id='id1' type='integer'>2</cn><apply id='id4'><ci id='id2'>u</ci><ci id='id3'>n</ci></apply><apply id='id7'><plus/><cn id='id5' type='rational'>1<sep/>2</cn><ci id='id6'>n</ci></apply><ci id='id8'>n</ci></apply><apply id='id23'><times/><apply id='id14'><ci id='id10'>u</ci><apply id='id13'><minus/><ci id='id11'>n</ci><cn id='id12' type='integer'>1</cn></apply></apply><apply id='id17'><plus/><cn id='id15' type='rational'>-1<sep/>2</cn><ci id='id16'>n</ci></apply><apply id='id22'><plus/><cn id='id18' type='rational'>-1<sep/>2</cn><apply id='id21'><times/><cn id='id19' type='integer'>3</cn><ci id='id20'>n</ci></apply></apply></apply><apply id='id35'><times/><apply id='id28'><ci id='id24'>u</ci><apply id='id27'><minus/><ci id='id25'>n</ci><cn id='id26' type='integer'>2</cn></apply></apply><apply id='id31'><plus/><cn id='id29' type='rational'>-3<sep/>2</cn><ci id='id30'>n</ci></apply><apply id='id34'><plus/><cn id='id32' type='rational'>-1<sep/>2</cn><ci id='id33'>n</ci></apply></apply></apply><cn id='id37' type='integer'>0</cn></apply></annotation-xml><annotation encoding='Maple'>2*u(n)*(1/2+n)*n+u(n-1)*(-1/2+n)*(-1/2+3*n)+u(n-2)*(-3/2+n)*(-1/2+n) = 0</annotation></semantics></math>

 This web site is compliant with HTML 4.01 and CSS 1. Copyright © 2001-2003 by the Algorithms Project and INRIA. All rights reserved. Created: Aug 1 2003 15:08:25.